Coleção da Caixa Geral de Depósitos : caraterização, salvaguarda e circulação - Coito, Jennifer Jade Oliveira do (2019)
This study intends to contribute to the knowledge of the Caixa Geral de Depósitos Collection, a corporate collection owned by the Portuguese banking institution Caixa Geral de Depósitos. This is one of the largest corporate art collections in the country, made up of works of lusophone contemporary art and is under the management of Caixa Geral de Depósitos Foundation - Culturgest. The foundation, as a managing agent and cultural entity, undertakes as part of its competencies the dissemination and the conservation of the Collection. Facing three decades since its constitution, the Collection has gone through different periods defined by the way it has been administered. Understanding the characteristics of the loans and the consequences they have on the preservation of the works of art involved, it was our goal to achieve a clear and objective reading of the different factors that contributed to the issues that have arisen around the safeguarding of the Collection. The first part of the study focuses on the characterisation of the Collection concerning its history, diffusion and conservation. The second part is based on the data regarding loans occurring between 1986 and 2017. The collection, analysis and interpretation of this data along with the existing directives published by revered organisations in the national and international museology field helped define the needs and priorities of the Colletion resulting in the proposition of guidelines for the elaboration of a loan policy